ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN MAHASISWA DALAM PEMILIHAN JURUSAN MENGGUNAKAN STRUCTURAL EQUATION MODELING (SEM) (Studi Kasus di Jurusan Statistika Universitas Diponegoro Semarang) - Allima Stefiana Insani; Abdul Hoyyi; Rita Rahmawati (Jurnal Gaussian, 2014)
University is an institution that provide educational service which has a wide variety of majors. Image of the university would affect the interest of new students in decision making process, as this will affect student satisfaction through the course. Many factors influence students decision in determining their aim majors, such as service quality, curriculum, environment and academic ability. These factors are latent variables then Structural Equation Modeling (SEM) used to determine factors effect that affect student satisfaction in selection of majors. The research conducted at Diponegoro University in Statistics Department. Overall model fit test obtain Goodness Of Fit on model with the value of GFI = 0,875 and         RMSEA = 0,084 are indicative of a good fit. In concluding the analysis, the factors that affect student satisfaction in decision to choose Statistics Department can be measured by academic ability, curriculum, and service quality. Students decision in choosing Statistics Department can be explained by the academic ability of students, the curriculum which is owned by Statistics Department and quality of service that is owned by the department of statistics at 96,9%. Statistics students satisfaction can be explained by academic ability of  students and student decision after choosing Statistics Department of 68,8%. Key words: Decision in choosing major, students satisfaction, Structural Equation Modeling